OPTIMIZATION OF SURGICAL TREATMENT OF ESOPHAGEAL ATRESIA IN NEWBORNS (World Bulletin of Public Health, 2025)
Esophageal atresia (AP) is one of the most severe malformations requiring emergency surgical treatment in the neonatal period. The frequency of occurrence is 1:3000-4500 live births. Despite significant advances in the surgical treatment of this pathology, mortality remains high and amounts to 15-50%, depending on concomitant malformations and birth weight.
Keywords: esophageal atresia; insurmountable diastasis; newborns